Experiential Learning to Enhance Work Skills, Empathy and Entrepreneurship in Business Schools - George, Manju P (Journal of Contemporary Research in Management (JCRM), 2016)
Abstract The characteristics of Y generation ​students who pursue their Masters degree in business schools necessitates the implementation of teaching strategies that engage and foster experiential learning . This article describes a four day long experiential learning project that was employed among students who pursue their regular management program​me​ ​at PSG Institute of Management, a leading B School in Coimbatore, Tamil Nadu. The primary purpose of the activity was to create social consciousness among students and to raise their level of understanding, about the world of an ordinary worker. The paper presents case studies that capture the experience, students had, and their response to this innovative teaching/learning endeavor. The results revealed that 88 percent of the students had positive attitude towards experiential learning project, and at the same time developed, work skills, empathy for workers, and knowledge towards entrepreneurial processes. Keywords: Experiential learning, Business Schools, Higher Education, Innovative Teaching, Social Consciousness, Management Education, Entrepreneurship Paper Type: Research Paper